Identification of a novel functional deletion variant in the 5'-UTR of the DJ-1 gene - Warnich Louise; Kinnear Craig; Venter Mauritz; van der Merwe Lize; Keyser Rowena J; Carr Jonathan; Bardien Soraya (BMC, 2009)
Abstract Background DJ-1 forms part of the neuronal cellular defence mechanism against oxidative insults, due to its ability to undergo self-oxidation. Oxidative stress has been implicated in the pathogenesis of central nervous system damage in different neurodegenerative disorders including Alzheimer's disease and Parkinson's disease (PD). Various mutations in the DJ-1 (PARK7) gene have been shown to cause the autosomal recessive form of PD. In the present study South African PD patients were screened for mutations in DJ-1 and we aimed to investigate the functional significance of a novel 16 bp deletion variant identified in one patient. Methods The possible effect of the deletion on promoter activity was investigated using a Dual-Luciferase Reporter assay. The DJ-1 5'-UTR region containing the sequence flanking the 16 bp deletion was cloned into a pGL4.10-Basic luciferase-reporter vector and transfected into HEK293 and BE(2)-M17 neuroblastoma cells. Promoter activity under hydrogen peroxide-induced oxidative stress conditions was also investigated. Computational (in silico) cis-regulatory analysis of DJ-1 promoter sequence was performed using the transcription factor-binding site database, TRANSFAC via the PATCH™ and rVISTA platforms. Results A novel 16 bp deletion variant (g.-6_+10del) was identified in DJ-1 which spans the transcription start site and is situated 93 bp 3' from a Sp1 site. The deletion caused a reduction in luciferase activity of approximately 47% in HEK293 cells and 60% in BE(2)-M17 cells compared to the wild-type (P < 0.0001), indicating the importance of the 16 bp sequence in transcription regulation. The activity of both constructs was up-regulated during oxidative stress. Bioinformatic analysis revealed putative binding sites for three transcription factors AhR, ARNT, HIF-1 within the 16 bp sequence. The frequency of the g.-6_+10del variant was determined to be 0.7% in South African PD patients (2 heterozygotes in 148 individuals). Conclusion This is the first report of a functional DJ-1 promoter variant, which has the potential to influence transcript stability or translation efficiency. Further work is necessary to determine the extent to which the g.-6_+10del variant affects the normal function of the DJ-1 promoter and whether this variant confers a risk for PD.